Critical Players and Gene Expression Regulation in Eucalyptus Xylogenesis - Carocha, Victor João Martins Taveira (2016)
Secondary xylem, commonly known as wood, is essentially formed by highly lignified secondary cell walls of both fibres and vessels. The process of formation of secondary xylem is also termed xylogenesis. Secondary xylem derives from the vascular cambium, whose dividing cells undergo irreversible differentiation, under a strict temporal and spatial control.(...)